Effects of dissolved oxygen, starvation, temperature, and salinity on the locomotive ability of juvenile Chinese shrimp Fenneropenaeus chinensis. Issue 2 (4th March 2019) - Li, Jiangtao; Li, Wentao; Zhang, Xiumei
Abstract : Locomotion is considered a fundamental property defining the fitness of animals. Shrimp locomotion includes walking, swimming, and tail-flipping. Little is known about the locomotive ability of juvenile shrimp. We studied the acute effects of key environmental factors on the ability of swimming and tail-flipping of juvenile Chinese shrimp Fenneropenaeus chinensis (1.10 ± 0.07 cm, body length), which was indicated by critical swimming speed ( U crit ) and tail-flipping speed ( U tail ), respectively. The key environmental factors include dissolved oxygen [DO; 2.2, 3.2, 4.2, 5.2, and 6.2 (control) mg L −1 ], starvation [1 (control), 3, 5, 7, and 9 days], temperature [9, 13, 17, 21 (control), and 25 °C (degrees Celsius)], and salinity [10, 15, 20, 25, and 30 (control) ppt]. The effect comparisons between these environmental factors were also obtained. Results showed that the changes of DO, starvation, temperature and salinity can affect not only the swimming, but also the tail-flipping of juvenile shrimp. The tail-flipping may be more important than swimming for survival in most shrimps, and therefore, U tail was more stable than U crit under hypoxia and starvation exposures. U crit and U tail showed similar sensibility to the changes of temperature and salinity. As in the effect comparison, U crit of juvenile F. chinensis was most affected by temperature, followed by DO and starvation, and the effect of salinity was the lowermost. These findings can be of value in understanding the physiological ecology of juvenile shrimp, and improving the stock enhancement of F. chinensis .